2016
DOI: 10.1007/s00167-016-4211-1
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of magnetic resonance imaging in evaluating meniscal and cartilage injuries in anterior cruciate ligament-deficient knees

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…MRI is a reliable tool for assessing meniscal tears and cartilage defects preoperatively, but it was reportedly more accurate for evaluating MMT than LMT. 30,31 It has also been reported that the sensitivity and negative predictive value for meniscal tears decrease in the presence of ACL tears, especially for LMT. 32 Thus, compared with MMT, the incidence of LMT in MRI studies may be underestimated in our series.…”
Section: Discussionmentioning
confidence: 97%
“…MRI is a reliable tool for assessing meniscal tears and cartilage defects preoperatively, but it was reportedly more accurate for evaluating MMT than LMT. 30,31 It has also been reported that the sensitivity and negative predictive value for meniscal tears decrease in the presence of ACL tears, especially for LMT. 32 Thus, compared with MMT, the incidence of LMT in MRI studies may be underestimated in our series.…”
Section: Discussionmentioning
confidence: 97%
“…In our study, we found 70% sensitivity with a specificity of 85%. It is well demonstrated in literature that MRI has a lower sensitivity in detecting lateral meniscus lesions, which some authors attribute to its anatomical structure [41]. Moreover, the location of a lesion impacts the diagnostic accuracy of MRI.…”
Section: Discussionmentioning
confidence: 99%
“…MRI and arthroscopy are still the benchmark non-invasive and invasive methods for the evaluation of meniscal tears, respectively. 21 - 23 …”
Section: Clinical Evaluationmentioning
confidence: 99%